2021
DOI: 10.5826/dpc.1104a90
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Sun Exposure Habits Between Individuals with High and Low Risk of Skin Cancer

Abstract: Background: Skin cancer incidence is rapidly increasing. The main risk factor, sun exposure, can be modified. Informational campaigns can be effective in raising skin cancer awareness and target the high-risk population. Still, sun exposure habits in people at high risk of skin cancer are not well-known. Objective: To investigate if and how sun exposure habits differ between low-risk and high-risk individuals. Methods: During the Swedish Euromelanoma campaign of 2018, questionnaires were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
6
2
2
Order By: Relevance
“…In contrast to previous findings ( 21 , 22 , 24 , 45 ), we did not observe a correlation between gender, Fitzpatrick skin type or a positive family history for melanoma and sun protective behavior. We assume that a comparison of our cohorts is generally difficult, since all were patients with an increased melanoma risk who voluntarily participated in the melanoma early detection study and might have had an increased awareness primarily.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous findings ( 21 , 22 , 24 , 45 ), we did not observe a correlation between gender, Fitzpatrick skin type or a positive family history for melanoma and sun protective behavior. We assume that a comparison of our cohorts is generally difficult, since all were patients with an increased melanoma risk who voluntarily participated in the melanoma early detection study and might have had an increased awareness primarily.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite observing suboptimal sun protection behavior in both at-risk and melanoma patients ( 21 , 23 25 , 27 , 29 , 45 ),, we found that compared to the general population ( 17 ), our study participants had already better sun protective behaviors before study enrollment. Nevertheless, we demonstrated that verbal education about sun protection during standard skin cancer screening by a dermatologist further improved sunscreen application frequency and SPF.…”
Section: Discussioncontrasting
confidence: 53%
“…[7] We might also have had some selection bias in which persons were more likely to bring the primary care physician's attention to a suspicious skin lesion. Alike prior studies investigating utilization of skin checks for skin cancer prevention, it is probable that there will be a higher proportion of young women, with a higher than average education level, as well as fair-skinned people attending these clinics [22]. However, we do not think this possible skewed selection of participants will have impacted the association between investigated risk factors and probability of performing a TBSE.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
“…3. Prevención Terciaria: todos los procedimientos que se realizan en los pacientes con cáncer con el fin de evitar las complicaciones clínicas y las recaídas (Karlsson et al, 2021).…”
Section: Medidas Preventivas Para Evitar El Cáncer De Pielunclassified